A hybrid model for pulsar's spin‐down evolution. Issue 9 (18th December 2019) - Gao, Zhi‐Fu; Wang, Hui; Peng, Qiu‐He; Shan, Hao; Wang, Na
Abstract: By considering the combined effects of both the standard magnetic dipole model and the composite neutron superfluid vortex model on pulsar's spin‐down, we study the evolution of pulsar's spin‐down on the P  −  P ˙ diagram. The evolution path of each pulsar is dictated by a particular mechanism in our hybrid model within different parameter spaces. The valley of each curve is the most possible place for a neutron star (NS) to be observed as this is the place corresponding to the minimum value of the evolution speed (i.e., the time derivative P ˙ ). In other words, pulsars would distribute around these valleys on the P  −  P ˙ diagram. The suppressed region in the lower‐right part of the diagram can be explained by neutrino cyclotron emission from the 1 S 0 neutron superfluid vortexes in NSs.